Impact of the learning context on undergraduate healthcare students’ Evidence-Based Practice confidence and attitudes (Health Education in Practice: Journal of Research for Professional Learning, 2018)
Evidence-based practice (EBP) is a complex process of enquiry and reasoning undertaken by practitioners to ensure defensible healthcare decisions are made. This study investigated the impact of different learning contexts on undergraduate healthcare students’ EBP confidence and attitudes. Within a broader project, 231 third- and fourth-year students in 20 undergraduate healthcare degrees in one Australian university completed an online survey. Students were asked to indicate: the context(s) in which they could remember learning EBP skills (in a research-focused subject, in a non-research-focused subject, and/or during workplace learning); their frequency of exposure to research articles in different learning contexts in the past year; and their levels of EBP confidence and other attitudinal target variables. There was no association between learning EBP skills in a research subject and any target variable. Learning EBP skills in a non-research (e.g., clinically focused) subject or during workplace learning was associated with higher levels of EBP confidence (p < 0.05) and pro-EBP attitudes. In addition, there was a positive relationship between exposure to research articles and EBP confidence, found to be strongest when exposure to the research occurred in the context of practice-based learning (r = 0.42, p < 0.001). The findings show that the curricular context in which EBP skills are taught impacts on students’ EBP confidence and attitudes. Teaching EBP skills in research-focused subjects may be necessary, but it is insufficient for maximising confidence and attitudes conducive to EBP. These findings are relevant to curriculum designers and educators seeking to enhance the effectiveness of undergraduate EBP education.